Comanthera borbae (Eriocaulaceae): a new species endemic to the Northern portion of the Chapada Diamantina, Bahia, Brazil - Pereira, Ana Carina Silva; Ribeiro, Patrícia Luz; Giulietti, Ana Maria (Phytotaxa, 2016)
A new species of Comanthera (Eriocaulaceae) from Brazil is described and illustrated. C. borbae is a perennial herb with a cushion habit, endemic to the rocky outcrops in the Northern part of the Chapada Diamantina, in the semi-arid region of Bahia state, here assessed as an endangered species. Its habitat and morphological variation are discussed, in comparison with C. pignalii and C. floccosa, also from Bahia.